A Critique of Educational Skills (Teaching Methods and Techniques) - Batool Sabzeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this research is to evaluate, criticize, and analyze the book in the field of teaching. The analytical method is used in book evaluation. The first example of the book Teaching and Learning Skills (Teaching Methods and Techniques) is the first volume by Hassan Shaabani. The textbook has been studied based on the content and format of academic textbook critique, textbook review, and humanities textbook review. Based on the research findings, this book has some advantages and disadvantages such as the introduction of goals and objectives at the beginning of each chapter, the use of tables and diagrams, the presentation of conceptual models at the beginning of each chapter, students’ professional needs, as well as shortcomings and weaknesses such as lacking a persuasive educational model, lack of new scientific findings, inadequate presentation, lack of motivational and critical thinking questions, and repeated disruption of some book topics with other related lessons. The other shortcomings include how to cite, overlooking new sources, adjust abstract, volume, and book cover design which are inappropriate to reduce book productivity and efficiency for the audience.